Silicalite-1 Membrane: Synthesis, Modification, Characterization And Its Performance For The Reactive Separation Of Para-Xylene From Xylene Isomers - Yeong , Yin Fong (2010)

(untitled)
Reactive separation of para-xylene from xylene isomers in a catalytic membrane reactor depends on the right choice of catalytic membrane. This membrane should not only catalyze xylene isomerization reaction but also separate para-xylene (p-xylene) from its isomers (ortho-xylene (o-xylene) and meta-xylene (m-xylene)). In the present study, silicalite-1 and two types of acid-functionalized silicalite-1 membranes: (1) propylsulfonic acid functionalized silicalite-1 membrane and (2) arenesulfonic acid-functionalized silicalite-1 membrane were synthesized on disc type -alumina support, pre-coated with mesoporous silica layer.